Restrictive v/s Routine episiotomy in Primigravida - Vachhani, Ashvin; Shah, Asmi; Kalathiya, Hetvi; Kapadiya, Jahanvi; Avaiya, Niyati; Patel, Zarana (International Journal of Innovative Research in Medical Science, 2022)
Introduction: Episiotomy is the surgical enlargement of the vaginal orifice by an incision on the perineum during the last part of the second stage of labour or delivery. Episiotomy is the most common surgical procedure experienced by women. In near past there were many studies pointed out its disadvantages like more post-delivery pain, wound complications and dyspareunia. So, this study was done to compare use of restrictive episiotomy and routine episiotomy in primigravidae undergoing vaginal birth. Aims and objectives: To assess the effects of restrictive use of episiotomy in comparison with routine episiotomy in primigravida during vaginal birth in terms of - (1) No. of episiotomies can be avoided (2) Perineal tear (3) Blood loss (4) Hematoma & Healing complications (5) Faecal & urinary incontinence (6) Dyspareunia. Material and methods: This study was descriptive analytic study conducted in the Department of Obstetrics and Gynecology, Surat municipal institute of medical education and research (SMIMER), Surat from January 2017 to June 2019 with sample size of 148 patients. Results: This study included total 148 patients, where 74 were selected randomly in each group. In Restrictive Episiotomy group, out of 74 patients, Episiotomy was required in 18 (24.32%) patients. Thus, Episiotomy was avoided in 56 (75.68%) patients. Mean duration of second stage of labour in Routine Episiotomy group was 31.88 ± 5.37min and in Restrictive Episiotomy group it was 32.35 ± 3.73min, which was suggestive of no statistically significant difference. (p value = 0.5375). Total 4.05% patients in Routine group and 13.51% patients in Restrictive group suffered from anterior vaginal tear which was statistically significant (p value = 0.021). There were 2 cases (18%) of 2nd degree perineal tear in routine episiotomy group which were 8(40%) in restrictive episiotomy group. The difference was statistically assessed by Chi-square and found to be significant (p value=0.2399). Not a single case of 3rd & 4th degree perineal tear in either group. In Routine Episiotomy group, suturing was done in 100% patients. While restricted episiotomy group only 44.59% needed suturing which was statistically significant (p value:<0.0001). Average blood loss in Routine group was 341.89 ± 49.33ml and in Restrictive group was 301.01 ± 52.41ml. So, there was significantly higher blood loss in Routine Episiotomy group. (p value= 0.000002). Complications rate in the form of episiotomy wound gap and hematoma was higher in routine group in 5.41% patients as compared to 1.35% patients in Restrictive group. Postpartum perineal pain at 1 week (14 v/s 5) and 2 weeks (5 v/s 1) was significantly higher in routine group as compared to the restrictive group. Postpartum perineal pain at 1 week and 2 weeks was significantly higher in routine group as compared to the restrictive group. Conclusion: In conclusion on the basis of our study, the immediate outcomes of routine episiotomy are no better than the restrictive use of episiotomy. Indeed, routine use is harmful to the degree that some proportion of women who would have had lesser injury instead had a surgical incision. The routine use of episiotomy has higher incidence of peripartum blood loss, requirement of suturing, postpartum perineal pain and healing complications. The policy of restrictive use of episiotomy is not associated with any third and fourth degree perineal tear or adverse neonatal outcomes.